Tendeiros de Beira de Estrada : caboclos - pluriativos de Fontoura Xavier - Cruz, Joseandra Sanderson da (2012)
This research aims to show the occupation and colonization of the region of Soledad, deepening the study in the municipality of Fontoura Xavier, with concentration in the tents on the edge of the highway. The central agents are traders who have tendeiros the BR 386 no Km 273 their tents, where commercial products and articles manufactured and produced by themselves. It is a life devoted to agriculture and trade activities by residents of the community of Vila Assisi, and small farmers as suppliers. The products are characteristic of the cultivation of their crops as beans, squash, peanuts, pine nuts, among others, expanding today to goods brought in from other places, such as leather carpets. The tents have emerged as a way to have jobs and income for the livelihood of families. Tents are thirty registered and established in that place. The Indian is the element that holds them featured by having been marginalized during the process of settling. Extractive activities exercised for landlords, especially the mate, had some small area assigned or occupied where withdrew their support on condition that exploited and subjugated. No organization at the start today, but in better conditions. The first tents were built in 1935 on the roadside, and wood. The Indian trader is better off today, more organized, because of incentives released by the Federal government and State and Municipal. The foundation of the Association of Tendeiros was essential for these improvements. In this practice the act tendeiros long time, passed from generation to generation the practice, knowledge, knowledge of dealing with trade. It was found that there were some advances and improvements in the functioning of this activity. New media marketing were implemented, including the use of credit cards as payment, the structure and location of the tents were evaluated in order to provide greater certainty for tendeiros and visitors. It is important to highlight the work (agriculture) of caboclo dealer, as well as crafts made by themselves. Emphasis is given to the event that happens every year: the Festival of the pinion. Because this product is found in abundance in the region, alleging a vast conservation of native Araucaria forest.